Glycerolysis-Based Reduction of Free Fatty Acids in Crude Palm Oil (CPO) for Cost Effective Biodiesel Pre-Treatment - Musa, Mursyid; Madon, Rais Hanizam; Roslan, Rohaizam; Mohd Salleh, Zuliazura; Abd Jalal, MZahar; Misdan, Nurasyikin; Hamdan, Mohamad Alif Hakimi; Madon, Rais Mohd Hazri (Journal of Advanced Mechanical Engineering Applications, 2025)
The high content of free fatty acids (FFA) in crude palm oil (CPO) presents a significant challenge for biodiesel production. This study investigates the glycerolysis pretreatment method using crude glycerol and potassium hydroxide (KOH) to reduce FFAs. Experiments were performed at varying molar ratios (1:3 to 1:9) and temperatures (60°C to 80°C). Results showed optimal FFA reduction at a 1:7 molar ratio and 80°C, reducing FFA below 5% within 60 minutes. FTIR analysis confirmed FFA conversion. The reaction followed a pseudo-second-order kinetic model (R² = 0.9832). Viscosity and density of the oil improved to 41.2 mPa·s and 0.886 g/cm³, respectively. These findings demonstrate that glycerolysis is a promising, eco-friendly, and cost-effective solution for pretreating high-FFA feedstock in biodiesel production.